Early Treatment with Nebulised Salbutamol Worsens Physiological Measures and Does Not Improve Survival Following Phosgene Induced Acute Lung Injury. Issue 2 (1st June 2009) - Grainge, C; Brown, R; Jugg, Bronwen; Smith, AJ; Mann, TM; Jenner, J; Rice, P; Parkhouse, DA
Abstract : Objectives: To examine the effectiveness of nebulised salbutamol in the treatment of phosgene induced acute lung injury. Method: Using previously validated methods, 12 anaesthetised large white pigs were exposed to phosgene (Ct 1978 ± 8 mg min m-3), established on mechanical ventilation and randomised to treatment with either nebulised salbutamol (2.5mg per dose) or saline control. Treatments were given 1, 5, 9, 13, 17 and 21 hours following phosgene exposure. The animals were followed to 24 hours following phosgene exposure. Results: Salbutamol treatment had no effect on mortality and had a deleterious effect on arterial oxygenation, shunt fraction and heart rate. There was a reduction in the number of neutrophils from 24.0% ± 4.4 to 12.17% ± 2.1 (p<0.05) in bronchoalveolar lavage, with some small decreases in inflammatory mediators in bronchoalveolar lavage but not in plasma. Conclusion: Nebulised salbutamol treatment following phosgene induced acute lung injury does not improve survival, and worsens various physiological parameters including arterial oxygen partial pressure and shunt fraction. Salbutamol treatment reduces neutrophil influx into the lung. Its sole use following phosgene exposure is not recommended.